The Impact of Digital Marketing and Mobile Applications on Service Innovation in German Companies - Makhmudov, Samariddin; Otakhonova, Dinora; Kulmanov, Toshmurod; Shamshiyeva, Nargizaxon; Juraev, Umidjon; Ruziev, Ganisher; Sabirova , Ullibibi (International Review of Management and Marketing, 2025)
This research examines how digital marketing and mobile app development enable service innovation in German companies during the period of 2005- 2024. Using firm-level panel data from the Moody’s Orbis database, firm-level panel data examines the relationships between social media advertising expenses, mobile app features, educational campaigns, total customers, and the rate of active digital users (used to approximate service innovation). By applying a Random Effects panel regression model, findings indicate that social media advertising, mobile app functionality, educational campaigns, and total customers have a significant and positive influence on firms’ rate of digital innovation performance. Findings show that consistently investing in digital engagement strategies and technological capabilities increases firms’ ability to innovate services, acquire customers, and build competitiveness within the changing digital economy in Germany. The present study provides new firm-level evidence for the digital transformation literature, as it illustrates that marketing and mobile technology work together to drive service innovation in advanced economies.